DNp73 enhances tumor progression and immune evasion in multiple myeloma by targeting the MYC and MYCN pathways - Liu, Lanting; Gong, Dasen; Sun, Hao; Feng, Fangshuo; Xu, Jie; Sun, Xiyue; Gong, Lixin; Yu, Zhen; Fang, Teng; Xu, Yan; Lyu, Rui; Wang, Tingyu; et al. (Frontiers in Immunology, 2024)
Multiple myeloma (MM) is an incurable hematological malignancy with high chromosome instability and heavy dependence on the immunosuppressive bone marrow microenvironment. P53 mutations are adverse prognostic factors in MM; however, clinically, some patients without P53 mutations also exhibit aggressive disease progression. DNp73, an inhibitor of TP53 tumor suppressor family members, drives drug resistance and cancer progression in several solid malignancies. Nevertheless, the biological functions of DNp73 and the molecular mechanisms in myelomagenesis remain unclear. Our study found that activation of NF-κB-p65 in multiple myeloma cells with different p53 mutation statuses upregulates DNp73 expression at the transcriptional level. Forced expression of DNp73 promoted aggressive proliferation and multidrug resistance in MM cells. Importantly, our study identified that DNp73 is involved in regulating MYCN and MYC expressions. Bulk RNA-seq analysis demonstrated increased levels of MYCN, MYC, and CDK7 with forced DNp73 expression in MM cells. A ChIP-qPCR assay revealed that DNp73 upregulates MYCN gene expression as a transcription factor. Additionally, DNp73 promoted immune evasion of MM cells by upregulating MYC target genes CD47 and PD-L1. Blockade of the CD47/SIRPα and PD-1/PD-L1 signaling pathways by the SIRPα-Fc fusion protein IMM01 and monoclonal antibody atezolizumab significantly restored the anti-MM activity of macrophages and T cells in the microenvironment, respectively. In summary, our study demonstrated for the first time that the p53 family member DNp73 remarkably induces proliferation, drug resistance, and immune escape of myeloma cells by directly targeting MYCN and regulating the MYC pathway. The oncogenic function of DNp73 is independent of p53 status in MM cells. These data contribute to a better understanding of the function of TP53 and its family members in tumorigenesis. Moreover, our study clarified that DNp73 overexpression not only promotes aggressive growth of tumor cells, but, more importantly, promotes immune escape of MM cells through upregulation of immune checkpoints. DNp73 could serve as a biomarker for immunotherapy targeting PD-L1 and CD47 blockade in MM patients.